Penggunaan Model Predict-Observ- Expail (POE) dalam Mengatasi Miskonsepsi Siswa SD materi Efek Rumah Kaca - Dwinta Syifva Liandi; Adrias Adrias; Salmaini Safitri Syam (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Misconseption are errors in understanding concepts than often occur in the context of science learning, particulary on the greenhouse effect, this study aims to address student’s misconceptions by implementing thePredict-Observe-Explain (POE) learning model in grade VI elementary school students. The study employed the Penelitian Tindakan Kelas (PTK) method based on the kemmis and McTggart model, which consists of four main stage: planning, implementation, observation, and reflection. The reseach subjek consisted of students from grade VI from SDN 13 Cingkariang. Data wewre Collected using Questionnaires and analyzed quantitatively based on pre-test and post-test result. The findings revealed the prior to that application of the POE model, only 15% of students had agoog understnading of the greenhouse effect, while 40% had partial understanding, and 45% did not understand the concept at all. After implementing the POE model, student’s understanding improve significantly, with 70% able to make accurate predictions. 80% actively involved in observation, ang 35% able to explain the greenhouse effect comprehensively. The implementation of the POE model has proven to be effective in correcting misconcepsions and improving student’s understanding through active and exploratory learning.